Advantages and disadvantages of retrenchment - Ismail, Fadillah; Chen, Chiaw Fen; Abdul Kadir, Adibah; Salim, Siti Aisyah; Chan, Shiau Wei; Ismail, Siti Norziah (Penerbit UTHM, 2020)
The stability of the job in a state or country usually depends on the condition of the economy in that country or state. Malaysia and many countries around the world have faced several economic downturns and recessions over the past year, this causes the slowdown of the economy and poor business conditions resulting in a slump in business due to the significant drop of the company’s profit. Companies that are suffering big losses may choose to restructure or reorganize their businesses to reduce the impact of poor business conditions. The wave of retrenchment usually hit the sectors of manufacturing, transportation, communication, commerce, and finance.